Influence of Media on Political Instability: Insights from International and National Case Studies - Shoaib, Muhammad; Anum, Isma; Latif, Tayyaba (Annals of Human and Social Sciences, 2025)
This paper examines the role of media in influencing political instability by investigating three significant case studies: the Pakistan Tehreek-e-Insaf (PTI) protest of 2014, the General Elections of 2018 in Pakistan, and the Arab Spring movement. By analyzing these case studies, the paper aims to investigate the impact of media on political instability as well as the intersection of media and politics. The paper discovers how traditional and digital media platforms work as reagents in determining public opinion mobilizing grassroots and manipulating political dynamics. Qualitative case study method was employed in this paper and the results revealed that the PTI protest of 2014 highlighted the impact of live media coverage and digital platforms in supporting long-term political tension. In the same way, the 2018 General Elections in Pakistan underlined the role of media in shaping electoral narratives and amplifying political division. The Arab Spring movement demonstrated the transformative power of social media in falling regimes and redefining power in the Middle East. By censoriously examining these events this paper highlights the dual-edged nature of media which can either strengthen democratic dissertation or aggravate political uncertainty. These findings emphasize the need for accountable media practices to certify balanced political outcomes as well as the monitoring of social media platforms by the governing authorities.